2019
DOI: 10.3390/su11051349
|View full text |Cite
|
Sign up to set email alerts
|

Labour Migration in the Middle Hills of Nepal: Consequences on Land Management Strategies

Abstract: Labour migration in Nepal is having profound effects on land management. We take two examples from the hills of Nepal where the increasing trend in outmigration continues unabated and explore its consequences. The purpose of this study is to understand the impacts of the subsequent labour shortage on land management and how it affects households. We used data from two surveys and assessed land use change and degradation with a qualitative mapping method. The findings show that the local context leads to very d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 41 publications
(28 reference statements)
1
37
0
1
Order By: Relevance
“…In other words, Nepal's past public policies on agricultural and rural development ignored mechanization in hillside farming systems because of a fear of labor displacement by the use of machines that could lead to large rural unemployment [47]. In hindsight, this was a clear failure to anticipate growing farm labor shortages, drudgery, and growing rural employment in the service sector, as well as opportunities for agri-food processing, marketing, and the influence of the growing remittance of the economy and labor [38,44,48,49]. [44]; MoAD [45]; Dahal et al [46].…”
Section: History Of Agricultural Innovation and Science Policymentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, Nepal's past public policies on agricultural and rural development ignored mechanization in hillside farming systems because of a fear of labor displacement by the use of machines that could lead to large rural unemployment [47]. In hindsight, this was a clear failure to anticipate growing farm labor shortages, drudgery, and growing rural employment in the service sector, as well as opportunities for agri-food processing, marketing, and the influence of the growing remittance of the economy and labor [38,44,48,49]. [44]; MoAD [45]; Dahal et al [46].…”
Section: History Of Agricultural Innovation and Science Policymentioning
confidence: 99%
“…In 2016, Nepal was the second (29.7%) country after Kyrgyzstan (35.4%) in the world in terms of receiving remittance [60]. One of the highest rates of out-migration in Nepal are from the hillside region and farmers are highly dependent on remittances received to support subsistence household expenditures [48].…”
Section: Agenda Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of climate change, high agricultural input costs, out-migration and long distances between residences and farmlands were perceived as the major factors driving farmland abandonment in the Hill region. A study based on household surveys found that labor shortages resulting from out-migration had caused farmland abandonment in the hilly and mountainous regions of Nepal [67]. In recent years, increasing labor costs have also contributed to farmland abandonment in many rural areas in China [68].…”
Section: Farmers' Perceptions About the Reasons For Farmland Abandonmentmentioning
confidence: 99%